Direct Somatic Embryogenesis in Rice (Oryza sativa L.) : Structural and Developmental Patterns - Totik Sri Mariani; Hiroshi Miyake; Yoji Takeoka (Jurnal Matematika & Sains, 2002)
In this study, we used light microscopy to observe the structural and developmental pattern during direct somatic embryogenesis in rice (Oryza sativa L). Initiation of somatic embryogenesis revealed the origin of somatic embryo. It was unicellular origin from the epidermis of scutellum zygotic embryo. The polarity of somatic embryo established when the elongated embryo flattened at the apical end. On the onset of scutellum development, the scutellar notch was formed. In germinated somatic embryo, the shoot apex was connected with the root by the vascular bundle strands. This is an important characteristic of somatic embryo. The result led us to the conclusion that rice somatic embryos underwent the same structural and developmental pattern as that of rice zygotic embryo.